1998
DOI: 10.2105/ajph.88.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation, weight gain, and changes in cardiovascular risk factors during menopause: the Healthy Women Study.

Abstract: OBJECTIVES: The relationship between smoking cessation, subsequent weight gain, and cardiovascular disease risk factors from premenopause to postmenopause was studied. METHODS: Healthy Women Study participants were assessed for changes in coronary heart disease risk factors from a premenopausal baseline assessment to first- and second-year postmenopausal assessments. RESULTS: Although ex-smokers gained substantially more weight than nonsmokers and smokers, they did not experience a greater increase in cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Women might have increased their dietary energy intake as a result of giving up smoking, since smoking cessation was shown to be associated with weight gain in perimenopausal and early postmenopausal women. 40 However, although there were slightly more smokers in this group, only three women in this group had given up smoking since the first visit.…”
Section: Weight Changesmentioning
confidence: 68%
“…Women might have increased their dietary energy intake as a result of giving up smoking, since smoking cessation was shown to be associated with weight gain in perimenopausal and early postmenopausal women. 40 However, although there were slightly more smokers in this group, only three women in this group had given up smoking since the first visit.…”
Section: Weight Changesmentioning
confidence: 68%
“…Most smokers will gain fewer than 5 kg after quitting, 70-73 a negligible health threat compared with the risks associated with continued smoking. 74 Since smoking cessation is the priority, aggressive treatment to fight the weight gain (e.g., strict dieting) are not recommended during a quit attempt. Once the patient has successfully quit smoking, he or she should be encouraged to maintain or adopt a healthy lifestyle, including exercise, eating plenty of fruits and vegetables, and limiting alcohol consumption.…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%
“…Men tend to have higher plasma LDL-C and lower HDL-C concentrations than comparably aged premenopausal women, and some studies have also reported higher VLDL-C, triglycerides, and apoB concentrations 9,10,12–17. Data from cross sectional9,10,17–24 and longitudinal studies23,2527 have shown that post- compared to premenopausal women have higher plasma total, LDL-C, VLDL-C, and triglyceride concentrations. It has been hypothesized that these differences might partly explain the lower CVD risk in premenopausal women and the higher but comparable CVD risk between postmenopausal women and men.…”
mentioning
confidence: 99%